1996
DOI: 10.1159/000276801
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Aminoglycoside Ototoxicity by Glutathione

Abstract: Aminoglycoside antibiotics are commonly used for the treatment of serious gram-negative infections despite a high incidence of associated ototoxicity. Attempts to elucidate the mechanisms of toxicity or prevent the adverse effects have previously been unsuccessful. Recently, the damaging effects of aminoglycosides on the inner ear have been shown to be caused by a metabolite of the drug, implying an enzymatic conversion of the parent compound. Glutathione has been suggested to be closely related to the detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…cochlear disruption by cisplatinum [23], GM [24], kanamycin [12,25], noise [26] and ischemia/reperfusion injury [27]. Conversely, administration of buthionine sulfoximine, an inhibitor of glutathione synthesis, potentiates the ototoxic effects of kanamycin and ethacrynic acid [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cochlear disruption by cisplatinum [23], GM [24], kanamycin [12,25], noise [26] and ischemia/reperfusion injury [27]. Conversely, administration of buthionine sulfoximine, an inhibitor of glutathione synthesis, potentiates the ototoxic effects of kanamycin and ethacrynic acid [28].…”
Section: Discussionmentioning
confidence: 99%
“…ROS generation is believed to contribute to pathological changes in a wide variety of etiologies, including all classic categories of ototoxic agents. The presence of ROS and their importance in hair cell death due to aminoglycosides is suggested by a number of studies that have demonstrated a prophylactic effect of antioxidants [7,12,13]. Concerning the interaction between ROS and NO in aminoglycoside ototoxicity, however, little is known to date.…”
Section: Introductionmentioning
confidence: 99%
“…Two strategies utilized to demonstrate the association between ROS formation and cochlear disruption are: (i) the use of ROS scavengers to protect against cochlear damage by agents that elicit ROS generation in other organ systems, and (ii) disturbance of the glutathione detoxification system, to potentiate ROSinduced ototoxicity. ROS scavengers have been shown to provide protection against cochlear disruption due to cisplatinum [26,27], gentamicin [28], kanamycin [15,29], noise [30] and ischemia/reperfusion injury [31,32]. Conversely, administration of buthionine sulfoximine, an inhibitor of glutathione synthesis, potentiates the ototoxic effects of kanamycin and ethacrynic acid [33].…”
Section: Discussionmentioning
confidence: 99%
“…ROS generation is believed to contribute to pathological changes in a wide variety of etiologies, including all classic categories of ototoxicants. The presence of ROS and their importance in hair cell death due to aminoglycosides is suggested by a number of studies that have demonstrated a protective effect of antioxidants [11,15,16]. NO in the inner ear mediates neurotransmission and may play an important role in regulating vascular tone, and in maintaining endolymph and ion homeostasis [8,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence. Guinea pigs treated with glutathione in combination with amikacin show reduced damage to the organ of Corti, compared to amikacin-only controls (40). In the Garetz report (41), Guinea pigs were injected with 100 mg/ kg/day gentamicin.…”
Section: Drug/compound: Glutathionementioning
confidence: 99%